A hydrogel composite proton exchange membrane and preparation method thereof
By using the preparation method of hydrogel composite proton exchange membrane in all vanadium flow batteries, the problem of membrane puncture risk under high compression ratio is solved, and higher battery performance and simplified industrial production are achieved.
Patent Information
- Application Number
- CN202411268590.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The risk of membrane puncture in existing all-vanadium flow batteries increases under high compression ratio conditions, resulting in attenuation of battery performance, and the existing proton exchange membrane hydrogel treatment technology is complex and not suitable for industrial production.
The preparation method of hydrogel composite proton exchange membrane is adopted. By swelling the proton exchange membrane and soaking it in the hydrogel precursor solution, a hydrogel layer rich in sulfonic acid groups is formed to enhance the resistance of the membrane to puncture and puncture. Tearing ability and functionalized processing of the finished sub-exchange membrane through simple immersion.
It improves the suitability of the proton exchange membrane under high compression ratio conditions and the efficient conduction ability of protons, reduces the risk of puncture, simplifies the preparation process, and is suitable for industrial production.
Smart Images

Figure CN118841610B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of all-vanadium liquid flow battery materials, and in particular relates to a hydrogel composite proton exchange membrane that can be used for an all-vanadium liquid flow battery and a preparation method thereof. Background Art
[0002] At present, my country's wind power and photovoltaic technologies are rapidly advancing, and the scale of installed capacity is constantly expanding. In view of the reality that renewable energy will be connected to the grid on a large scale, energy storage can greatly improve the reliability of wind power and photovoltaic power generation. All-vanadium liquid flow batteries (abbreviated as vanadium batteries, VRFB) rely on their own advantages such as safety, reliability, and long cycle life. In the fields of new energy power generation and smart grid construction, they have a relatively broad application prospect, but due to the high initial system construction cost, they are subject to certain restrictions in commercial application.
[0003] One of the effective ways to reduce the cost of all-vanadium liquid flow battery systems is to increase power density by reducing battery polarization. Ohmic polarization is an important component of battery internal resistance, which depends to a large extent on the degree of compression of the electrode. As the electrode compression rate increases, its ohmic internal resistance will decrease. However, with the further increase of the electrode compression ratio, the side effects of the membrane being squeezed by the electrode are more significant, the risk of the carbon fiber on the membrane side of the electrode piercing the proton membrane increases, and the deformation of the membrane itself is aggravated. These adverse effects may cause the battery performance to decay. Therefore, high power density also has higher requirements for the proton conductivity, mechanical strength and chemical stability of the membrane material. Therefore, based on the current commercial proton exchange membrane, it is of great significance to develop a membrane material that is more suitable for high compression ratio conditions and stable operation at high power density. Summary of the invention
[0004] The present invention aims at the problems existing in the prior art and provides a hydrogel composite proton exchange membrane and a preparation method thereof. The present invention first performs a swelling treatment on the proton exchange membrane, then soaks the swelling proton exchange membrane in a hydrogel precursor solution, and sequentially obtains a hydrogel composite proton exchange membrane by free radical polymerization, water washing, acid washing, and drying. The proton exchange membrane of the present invention adds a hydrogel layer on the membrane surface, which improves the ability to resist puncture and tearing while ensuring the integrity of the structure of the proton exchange membrane, such as the finished proton exchange membrane, and can meet its applicability under higher compression ratio conditions. In addition, the hydrogel layer uses a monomer with a sulfonic acid group, and the uniformly distributed sulfonic acid group is connected to the polymer network in the form of a covalent bond, which has a high water retention capacity and is conducive to the efficient transfer of protons. Compared with the existing proton exchange membrane hydrogel processing technology, the present invention can perform subsequent functionalization treatment on the finished proton exchange membrane only by soaking, which is suitable for most finished proton exchange membranes, and the preparation method is simpler, the conditions are milder, and it is more favorable to achieve industrialization. Specifically, one aspect of the present invention provides a method for preparing a hydrogel composite proton exchange membrane, the method for preparing the proton exchange membrane comprising the following steps:
[0005] S1: soaking a proton exchange membrane in static water, wherein the proton exchange membrane is a sulfonic acid membrane, the soaking temperature is 20-40°C, the soaking time is 12-24 hours, and a swollen proton exchange membrane is obtained for standby use;
[0006] S2: dissolving 2-acrylamide-2-methylpropanesulfonic acid (AMPS) and N,N'-methylenebisacrylamide (MBAA) in water, and stirring evenly to obtain an AMPS / MBAA mixed solution; adding an initiator to the AMPS / MBAA mixed solution, and mixing evenly to obtain a hydrogel precursor solution for standby use; in the hydrogel precursor solution, the mass fraction of AMPS is 1% to 5%, the mass fraction of MBAA is 0.02% to 0.1%, and the mass fraction of the initiator is 0.02% to 0.1%;
[0007] S3: immersing the swollen proton exchange membrane obtained in step S1 in the hydrogel precursor solution prepared in step S2, taking it out after immersion for 5 to 10 minutes, and drying the proton exchange membrane after immersion in the hydrogel precursor solution at 40 to 60° C. for 6 to 24 hours, thereby forming a hydrogel layer on the surface of the proton exchange membrane;
[0008] S4: washing the proton exchange membrane prepared in step S3;
[0009] S5: using an acid solution to acid-wash the proton exchange membrane washed in step S4, and drying the membrane to obtain a hydrogel composite proton exchange membrane.
[0010] In one or more embodiments, the proton exchange membrane in step S1 is a homogeneous membrane or a composite membrane, the homogeneous membrane is a perfluorosulfonic acid membrane, a partially fluorinated sulfonic acid membrane or a non-fluorinated sulfonic acid membrane, and the composite membrane is a perfluorosulfonic acid membrane, a partially fluorinated sulfonic acid membrane or a non-fluorinated sulfonic acid membrane containing a PTFE reinforcement layer.
[0011] In one or more embodiments, in step S2, the mass ratio of AMPS to MBAA is 50:1 to 120:1.
[0012] In one or more embodiments, the initiator used in step S2 is a persulfate.
[0013] In one or more embodiments, the initiator is one or more selected from potassium persulfate, sodium persulfate, and ammonium persulfate.
[0014] In one or more embodiments, in step S2, after the initiator is added, ultrasonic mixing is performed.
[0015] In one or more embodiments, in step S4, the water washing is to soak the proton exchange membrane obtained in step S3 in water for 24 to 48 hours, during which the water is changed 4 to 8 times.
[0016] In one or more embodiments, step S5 has one or more of the following features:
[0017] The acid washing is to soak the washed proton exchange membrane in an acid solution for 1 to 3 hours;
[0018] The concentration of the acid solution is 0.01 mol / L to 1 mol / L;
[0019] The acid solution is dilute sulfuric acid;
[0020] The drying is performed at 40-60°C for 1-3 hours;
[0021] The hydrogel composite proton exchange membrane obtained in step S5 is 2-10 μm thicker than the proton exchange membrane before immersion in step S1.
[0022] Another aspect of the present invention provides a hydrogel composite proton exchange membrane, which is prepared by the method for preparing a hydrogel composite proton exchange membrane of the present invention.
[0023] Another aspect of the present invention provides an all-vanadium redox flow battery, which contains the hydrogel composite proton exchange membrane of the present invention.
[0024] Compared with the prior art, the present invention has the following beneficial effects: the hydrogel composite proton exchange membrane of the present invention adds a hydrogel layer, and the hydrogel forms a kind of "elastomer"-like protection on the surface of the proton exchange membrane, which can reduce the risk of puncture of the proton exchange membrane under the condition of high compression ratio of the electrode, has better ability to resist puncture and tearing, can meet its applicability under higher compression ratio conditions, and contains rich sulfonic acid groups, which is conducive to the rapid conduction of protons. The hydrogel layer uses a monomer with a sulfonic acid group, and the evenly distributed sulfonic acid groups are connected to the polymer network in the form of covalent bonds, which has a high water retention capacity and is conducive to the efficient transfer of protons. Compared with the existing proton exchange membrane hydrogel processing technology, the preparation method of the present invention is simple, the conditions are mild, and it is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the structure of a hydrogel composite proton exchange membrane in some embodiments of the present invention.
[0026] Figure 2 This is a comparison chart of the coulombic efficiency (CE) of the all-vanadium redox flow batteries assembled using the proton exchange membranes of Examples 1-2 and Comparative Examples 1-2 in the present invention.
[0027] Figure 3 This is a comparison chart of the voltage efficiency (VE) of the all-vanadium liquid flow batteries assembled using the proton exchange membranes of Examples 1-2 and Comparative Examples 1-2 in the present invention.
[0028] Figure 4 This is a comparison chart of the energy efficiency (EE) of the all-vanadium redox flow batteries assembled using the proton exchange membranes of Examples 1-2 and Comparative Examples 1-2 in the present invention.
[0029] Figure 5 This is a graph showing the relationship between the coulombic efficiency, voltage efficiency, energy efficiency and the number of cycles of the all-vanadium liquid flow battery assembled using the proton exchange membrane of Example 1 in the present invention.
[0030] Figure 6 This is a graph showing the relationship between the coulombic efficiency, voltage efficiency, energy efficiency and the number of cycles of the all-vanadium liquid flow battery assembled using the proton exchange membrane of Comparative Example 1 in the present invention.
[0031] Figure 7 It is the maximum puncture resistance of the proton exchange membranes of Examples 1-2 and Comparative Examples 1-2 in the present invention.
[0032] Figure 8 It is the tensile strength of the proton exchange membranes of Examples 1-2 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this document. Unless otherwise specified, all technical and scientific terms used in this document have the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this specification shall prevail.
[0034] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0035] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0036] In this document, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values within the range (including integers and fractions).
[0037] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0038] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope defined by the present invention.
[0039] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0040] The present invention proposes a hydrogel composite proton exchange membrane and a preparation method thereof. In the present invention, the proton exchange membrane is first subjected to a swelling treatment, and then the swollen proton exchange membrane is immersed in a hydrogel precursor solution, and then free radical polymerization, water washing, acid washing, and drying are performed in sequence to obtain a hydrogel composite proton exchange membrane. A hydrogel layer is added to the surface of the proton exchange membrane, which has a better ability to resist puncture and tearing, and can meet its applicability under higher compression ratio conditions. In addition, the hydrogel layer uses a monomer with a sulfonic acid group, and the evenly distributed sulfonic acid group is connected to the polymer network in the form of a covalent bond, has a high water retention capacity, and is conducive to the efficient transfer of protons. Compared with the existing proton exchange membrane hydrogel processing technology, the preparation method of the present invention is simple, the conditions are mild, and it is easy to realize industrialization.
[0041] In some embodiments, the structure of the hydrogel composite proton exchange membrane of the present invention is as follows Figure 1 As shown, the surface of the proton exchange membrane has a hydrogel layer rich in sulfonic acid groups, which is conducive to the rapid passage of protons.
[0042] The method for preparing a hydrogel composite proton exchange membrane of the present invention comprises the following steps:
[0043] S1: soaking the proton exchange membrane in static water at a temperature of 20-40°C for a time of 12-24 h to obtain a swollen proton exchange membrane for standby use;
[0044] S2: dissolving AMPS and MBAA in water, stirring evenly to obtain an AMPS / MBAA mixed solution; adding an initiator to the AMPS / MBAA mixed solution, mixing evenly to obtain a hydrogel precursor solution for standby use; in the hydrogel precursor solution, the mass fraction of AMPS is 1% to 5%, the mass fraction of MBAA is 0.02% to 0.1%, and the mass fraction of the initiator is 0.02% to 0.1%;
[0045] S3: immersing the swollen proton exchange membrane obtained in step S1 in the hydrogel precursor solution prepared in step S2, taking it out after immersion for 5 to 10 minutes, and drying the proton exchange membrane after immersion in the hydrogel precursor solution at 40 to 60° C. for 6 to 24 hours;
[0046] S4: washing the proton exchange membrane prepared in step S3;
[0047] S5: using an acid solution to acid-wash the proton exchange membrane washed in step S4, and drying the membrane to obtain a hydrogel composite proton exchange membrane.
[0048] In the present invention, AMPS as a monomer has more sulfonic acid groups, which can ensure that the hydrogel layer has the ability to conduct hydrogen protons.
[0049] In the present invention, MBAA is a conventional and active cross-linking agent, which can rapidly and efficiently transform the high molecular polymer from a linear structure to a three-dimensional network structure.
[0050] In the present invention, in step S1, the purpose of swelling is to take into account that the size of the hydrogel will change during the drying or water absorption process. In order to prevent the proton exchange membrane itself from being stretched or shrunk to a large extent due to the size change of the hydrogel, the proton exchange membrane is fully swollen in the early stage of preparation to reduce the risk of inconsistent size change rates of the two components in the subsequent preparation.
[0051] The proton exchange membrane used in the present invention is a sulfonic acid membrane. The initial thickness of the proton exchange membrane used in the present invention can be 45 to 55 μm. The proton exchange membrane can be a homogeneous membrane or a composite membrane. The homogeneous membrane can be a perfluorosulfonic acid membrane, a partially fluorinated sulfonic acid membrane or a non-fluorinated sulfonic acid membrane. The composite membrane can be a PTFE-enhanced perfluorosulfonic acid membrane, a partially fluorinated sulfonic acid membrane or a non-fluorinated sulfonic acid membrane. It is understood that the sulfonic acid proton exchange membrane used in the present invention mainly conducts protons through ion channels, and there is no pore structure inside, so the hydrogel layer can be generated on the membrane surface. Porous membranes (such as polysulfone membranes, polyamide membranes, polyphenylene ether membranes, and polybenzimidazole membranes, etc.) will cause the hydrogel precursor solution to enter the internal pores and cannot form a hydrogel layer on the membrane surface. The hydrogel inside the pores will destroy the structure of the porous membrane itself, and cannot form a puncture-proof protective layer, and the purpose of the present invention cannot be achieved.
[0052] In some embodiments, the proton exchange membrane used in step S1 is a perfluorosulfonic acid proton exchange membrane of model N-212 with a thickness of 50 μm and a size of 9.0 cm×11.5 cm.
[0053] In the present invention, the soaking temperature in step S1 is 20-40°C, for example, 25°C, 30°C, or 35°C.
[0054] In the present invention, the soaking time in step S1 is 12 to 24 h, for example, 14 h, 16 h, 18 h, 20 h, or 22 h.
[0055] In the present invention, in step S2, the mass fraction of AMPS in the hydrogel precursor solution is 1% to 5%, such as 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, and 4.5%. In some preferred embodiments, the mass fraction of AMPS in the hydrogel precursor solution is 2% to 2.5%, such as 2.1%, 2.2%, 2.3%, and 2.4%, which is conducive to improving the proton conductivity of the proton exchange membrane, thereby improving the coulombic efficiency of the battery.
[0056] In the present invention, in step S2, the mass fraction of MBAA in the hydrogel precursor solution is 0.02% to 0.1%, for example, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, and 0.09%.
[0057] In the present invention, in step S2, the mass ratio of AMPS to MBAA in the hydrogel precursor solution can be 50: 1 to 120: 1, such as 55: 1, 60: 1, 65: 1, 70: 1, 75: 1, 80: 1, 85: 1, 90: 1, 95: 1, 100: 1, 105: 1, 110: 1, 115: 1, 120: 1. In some preferred embodiments, the mass ratio of AMPS to MBAA in the hydrogel precursor solution is 55: 1 to 65: 1, such as 58: 1, 60: 1, 62: 1, which is conducive to improving the proton conductivity of the proton exchange membrane, thereby improving the coulombic efficiency of the all-vanadium redox flow battery.
[0058] In the present invention, in step S2, after the initiator is added, ultrasonic mixing is performed, and the ultrasonic time is 2 to 5 minutes, for example, 3 minutes, 4 minutes.
[0059] In the present invention, in step S2, the mass fraction of the initiator in the hydrogel precursor solution is 0.02% to 0.1%, for example, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, and 0.09%.
[0060] In the present invention, in step S3, the purpose of placing the proton exchange membrane after being soaked in the hydrogel precursor solution in an oven is to cause a self-polymerization reaction.
[0061] In the present invention, in step S3, the proton exchange membrane is immersed in the hydrogel precursor solution for 5 to 10 min, for example, 6 min, 7 min, 8 min, or 9 min.
[0062] In the present invention, the proton exchange membrane after being soaked in the hydrogel precursor solution in step S3 is dried at 40-60°C, for example, 45°C, 50°C, or 55°C.
[0063] In the present invention, the drying time of the proton exchange membrane after being soaked in the hydrogel precursor solution in step S3 is 6 to 24 hours, for example, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, and 22 hours.
[0064] In the present invention, in step S4, the purpose of soaking and washing the proton exchange membrane obtained in step S3 in water is to remove unreacted chemical substances and improve the purity of the hydrogel.
[0065] In the present invention, in step S4, the proton exchange membrane prepared in step S3 can be immersed in water for 24 to 48 hours, for example, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, and 46 hours. In step S4, the water can be changed 4 to 8 times during the immersion process.
[0066] In the present invention, in step S5, the purpose of acid washing the proton exchange membrane obtained in step S4 with an acid solution is to activate the proton membrane. The acid washing method can be to soak the proton exchange membrane in the acid solution for 1 to 3 hours, such as 1.5 hours, 2 hours, or 2.5 hours. The acid solution can be dilute sulfuric acid.
[0067] In the present invention, the concentration of the acid solution used in step S5 can be 0.01 mol / L~1 mol / L, for example, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L.
[0068] In some embodiments, in step S5, the proton exchange membrane prepared in step S4 is soaked in dilute sulfuric acid for 1 to 3 hours.
[0069] In the present invention, in step S5, the drying temperature of the proton exchange membrane obtained after acid washing can be 40-60°C, for example, 45°C, 50°C, or 55°C.
[0070] In the present invention, in step S5, the drying time of the proton exchange membrane obtained after acid washing can be 1 to 3 h, for example, 1.5 h, 2 h, or 2.5 h.
[0071] In the present invention, the proton exchange membrane is immersed in a hydrogel precursor solution, which is conducive to obtaining a thinner hydrogel composite membrane. The thickness of the proton exchange membrane after the composite hydrogel is preferably 2-10 μm, more preferably 2-7 μm, such as 3 μm, 4 μm, 5 μm, 6 μm.
[0072] The thickness of the hydrogel composite proton exchange membrane of the present invention can be 50-60 μm, for example, 51 μm, 52 μm, 53 μm, 54 μm, 55 μm, 56 μm, 57 μm, 58 μm, 59 μm, 60 μm. In some preferred embodiments, the thickness of the hydrogel composite proton exchange membrane is 53-57 μm, which is conducive to improving the puncture resistance and tear resistance of the proton exchange membrane, while improving the proton conductivity of the proton exchange membrane, thereby improving the coulombic efficiency of the all-vanadium redox flow battery.
[0073] The hydrogel composite proton exchange membrane of the present invention can be used to assemble an all-vanadium liquid flow battery.
[0074] The present invention will be described below in the form of specific examples. It should be understood that these examples are illustrative only and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The compounds in the examples can all be purchased through commercial routes.
[0075] Example 1
[0076] This example uses the following steps to prepare a hydrogel composite proton exchange membrane:
[0077] S1: Soak a perfluorosulfonic acid proton exchange membrane (Suzhou Kerun, model N-212, thickness 50 μm) with a specification of 9.0 cm×11.5 cm in static deionized water at a soaking temperature of 25°C for 12 h to obtain a swollen proton exchange membrane for use.
[0078] S2: Dissolve 600 mg of AMPS and 10 mg of MBAA in 25 mL of deionized water and stir to obtain an AMPS / MBAA mixed solution. Weigh 12 mg of potassium persulfate (K2S2O8) as an initiator and dissolve it in 1 mL of deionized water to obtain an initiator solution. Add the initiator solution to the prepared AMPS / MBAA mixed solution and ultrasonicate for 3 min to obtain a hydrogel precursor solution for later use.
[0079] S3: Immerse the swollen proton exchange membrane obtained in step S1 in the hydrogel precursor solution prepared in step S2, take it out after soaking for 10 minutes, and place the proton exchange membrane soaked in the hydrogel precursor solution in an oven at 50° C. to dry for 12 hours.
[0080] S4: Soak the proton exchange membrane prepared in step S3 in 500 mL of deionized water for 36 h, and replace the deionized water every 4 h.
[0081] S5: Soak the proton exchange membrane washed with water in step S4 in a 0.05 mol / L dilute sulfuric acid solution for 2 h, and then dry it in an oven at 40° C. for 2 h to obtain a hydrogel composite proton exchange membrane with a thickness of about 55 μm.
[0082] Example 2
[0083] S1: Soak a perfluorosulfonic acid proton exchange membrane (Suzhou Kerun, model N-212, thickness 50 μm) with a specification of 9.0 cm×11.5 cm in static deionized water at a soaking temperature of 25°C for 12 h to obtain a swollen proton exchange membrane for use.
[0084] S2: Dissolve 1100 mg of AMPS and 10 mg of MBAA in 25 mL of deionized water and stir to obtain an AMPS / MBAA mixed solution. Weigh 26 mg of K2S2O8 as an initiator and dissolve it in 1 mL of deionized water to obtain an initiator solution. Add the initiator solution to the prepared AMPS / MBAA mixed solution and ultrasonicate for 3 min to obtain a hydrogel precursor solution for later use.
[0085] S3: Immerse the swollen proton exchange membrane obtained in step S1 in the hydrogel precursor solution prepared in step S2, take it out after soaking for 10 minutes, and place the proton exchange membrane soaked in the hydrogel precursor solution in an oven at 50° C. to dry for 12 hours.
[0086] S4: Soak the proton exchange membrane prepared in step S3 in 500 mL of deionized water for 36 h, and replace the deionized water every 4 h.
[0087] S5: Soak the proton exchange membrane washed with water in step S4 in a 0.05 mol / L dilute sulfuric acid solution for 2 h, and then dry it in an oven at 40° C. for 2 h to obtain a hydrogel composite proton exchange membrane with a thickness of about 60 μm.
[0088] Comparative Example 1
[0089] The proton exchange membrane used in Comparative Example 1 is a perfluorosulfonic acid proton exchange membrane with a model of N-212 and a thickness of 50 μm and a size of 9.0 cm×11.5 cm produced by Suzhou Kerun Company.
[0090] Comparative Example 2
[0091] Comparative Example 2: A hydrogel composite membrane was prepared using a polysulfone porous membrane by the following steps:
[0092] S1: 0.8 g of polysulfone (Solvay, model P-3500) was dispersed in a mixed solvent of 2.5 mL of N-methylpyrrolidone (NMP) and 0.8 mL of ethanol and stirred at room temperature for 24 h to form a uniform viscous polymer solution.
[0093] S2: The polymer solution obtained in step S1 is allowed to stand overnight to eliminate bubbles, and then the polymer solution is poured onto a clean and tidy glass plate to be naturally cast. The glass plate is quickly immersed in a mixed solution of NMP and deionized water in a volume ratio of 1:1 for 24 hours to form a cast film on the glass plate.
[0094] S3: The cast film obtained in step S2 is directly transferred from the mixed solution of NMP and deionized water to the hydrogel precursor solution prepared in step S2 of Example 1 and immersed for 2 h.
[0095] S4: The cast film soaked in step S3 is sandwiched between two transparent glass plates and irradiated with UV in a UV curing machine for 2 hours to polymerize the monomers.
[0096] S5: Soak the cured membrane in step S4 in 500 mL of deionized water for 36 h, and replace the deionized water every 4 h.
[0097] S6: Soak the membrane washed with water in step S5 in a 0.05 mol / L dilute sulfuric acid solution for 2 h, and then dry it in an oven at 40° C. for 2 h to obtain a hydrogel-composite porous polysulfone membrane with a thickness of about 55 μm.
[0098] Test Example 1
[0099] 1. Battery assembly
[0100] The hydrogel composite proton exchange membrane prepared in Examples 1-2, the perfluorosulfonic acid proton exchange membrane in Comparative Example 1, and the hydrogel composite porous polysulfone membrane in Comparative Example 2 were respectively assembled into an all-vanadium redox flow battery:
[0101] The active material in the cathode electrolyte of the all-vanadium redox flow battery is 1.7 mol / L V 4+ / V 5+ solution, the active substance in the negative electrode electrolyte is 1.7 mol / L V 2+ / V 3+ solution, the supporting electrolyte was 4 mol / L sulfuric acid, the volume of the positive and negative electrolytes was 70 mL, the carbon felt (2.5 mm) was produced by Liaoyang Jingu, and the effective area of the carbon felt electrode was 48 cm 2 , the compression ratio is 40%~45%.
[0102] 2. Characteristic test (Coulomb efficiency, voltage efficiency, energy efficiency): constant current test, current density is 80, 110, 150, 200, 250, 300 mA / cm 2 The upper limit of charge is 1.55 V and the lower limit of discharge is 1.00 V. The test results are as follows Figure 2-4 As shown, CE represents coulombic efficiency, VE represents voltage efficiency, and EE represents energy efficiency.
[0103] 3. Stability test: constant current test at 200 mA / cm 2 The charge and discharge cycles were continuously performed for 1000 times, with the upper limit of charge being 1.55 V and the lower limit of discharge being 1.00 V. The test results are shown in Figure 5-6 As shown, CE represents coulombic efficiency, VE represents voltage efficiency, and EE represents energy efficiency.
[0104] 4. Maximum puncture resistance test: refer to GB / T 37841-2019, clamp the sample between the puncture instrument fixtures, and puncture the sample at a speed of 50 mm / min until the puncture needle punctures the sample, and obtain the maximum puncture resistance of the membrane at this time.
[0105] 5. Tensile strength: refer to NB / T 42080-2023, fix the sample on the fixture of the universal testing machine, stretch the sample at a speed of 200 mm / min, and record the load value when the sample breaks to calculate the tensile strength of the sample.
[0106] from Figure 2 It can be seen that the coulombic efficiency of the all-vanadium liquid flow cell assembled using Examples 1 and 2 is better than that of Comparative Example 1 and close to that of Comparative Example 2, which indicates that the hydrogel composite proton exchange membrane obtained by the treatment of the present invention has good proton conductivity and the coulombic efficiency is close to that of the porous membrane.
[0107] from Figure 3 It can be seen that the voltage efficiency of the all-vanadium liquid flow cell assembled using Examples 1 and 2 is not much different from that of Comparative Example 1, but is significantly higher than that of Comparative Example 2, which indicates that the hydrogel layer on the surface of the composite membrane of the present invention does not increase the internal resistance of the battery, while the porous membrane of Comparative Example 2 contains a hydrogel network, which causes the structure of the membrane itself to be destroyed and the internal resistance of the membrane to increase sharply.
[0108] from Figure 4 It can be seen that the energy efficiency of the embodiment is higher than that of the comparative example as a whole. Compared with Example 1, the membrane thickness of the hydrogel composite proton exchange membrane obtained in Example 2 is larger, the proton conduction path is increased, thereby increasing the conduction resistance and reducing the conduction rate, so the coulombic efficiency is not significantly improved.
[0109] from Figure 5 , 6 It can be seen that after 1000 cycles of charge and discharge, the coulombic efficiency, voltage efficiency and energy efficiency of Example 1 did not show obvious attenuation; while the coulombic efficiency and voltage efficiency of Comparative Example 1 dropped sharply after 800 cycles, and the overall energy efficiency attenuated seriously. Therefore, the hydrogel composite proton exchange membrane prepared by the present invention has better initial electrochemical performance and stability.
[0110] Figure 7 , Figure 8 The maximum puncture resistance and tensile strength of Examples 1-2 and Comparative Examples 1-2 were compared respectively. Compared with Comparative Example 1, the hydrogel composite proton exchange membrane of Example 1-2 has significantly improved resistance to puncture and tearing due to the addition of a hydrogel protective layer. The maximum puncture resistance and tensile strength of Comparative Example 2 are significantly lower than those of Comparative Example 1. This is because in Comparative Example 2, the hydrogel precursor solution basically penetrates into the internal pores of the porous membrane, and no buffer protective layer is generated on the membrane surface; compared with the structural network of a single component, the polymerization and connection of the two components of hydrogel and polysulfone are more difficult, resulting in defects in the membrane itself and poor uniformity, resulting in low puncture resistance.
Claims
1. A method for preparing a hydrogel composite proton exchange membrane, characterized in that: The method comprises the following steps: S1: soaking a proton exchange membrane in static water, wherein the proton exchange membrane is a sulfonic acid membrane, the soaking temperature is 20-40° C., the soaking time is 12-24 h, and a swollen proton exchange membrane is obtained for standby use; S2: dissolving 2-acrylamide-2-methylpropane sulfonic acid and N,N'-methylenebisacrylamide in water, and stirring evenly to obtain a 2-acrylamide-2-methylpropane sulfonic acid / N,N'-methylenebisacrylamide mixed solution; adding an initiator to the 2-acrylamide-2-methylpropane sulfonic acid / N,N'-methylenebisacrylamide mixed solution, and mixing evenly to obtain a hydrogel precursor solution for standby use; in the hydrogel precursor solution, the mass fraction of 2-acrylamide-2-methylpropane sulfonic acid is 1% to 5%, the mass fraction of N,N'-methylenebisacrylamide is 0.02% to 0.1%, and the mass fraction of the initiator is 0.02% to 0.1%; S3: immersing the swollen proton exchange membrane obtained in step S1 in the hydrogel precursor solution prepared in step S2, taking it out after immersion for 5 to 10 minutes, and drying the proton exchange membrane after immersion in the hydrogel precursor solution at 40 to 60° C. for 6 to 24 hours, thereby forming a hydrogel layer on the surface of the proton exchange membrane; S4: washing the proton exchange membrane prepared in step S3; S5: using an acid solution to acid-wash the proton exchange membrane washed in step S4, and drying the membrane to obtain a hydrogel composite proton exchange membrane.
2. The method according to claim 1, characterized in that In step S1, the proton exchange membrane is a homogeneous membrane or a composite membrane, the homogeneous membrane is a perfluorosulfonic acid membrane, a partially fluorinated sulfonic acid membrane or a non-fluorinated sulfonic acid membrane, and the composite membrane is a perfluorosulfonic acid membrane, a partially fluorinated sulfonic acid membrane or a non-fluorinated sulfonic acid membrane containing a PTFE reinforcement layer.
3. The method according to claim 1, characterized in that In step S2, the mass ratio of 2-acrylamide-2-methylpropanesulfonic acid to N,N'-methylenebisacrylamide is 50:1-120:
1.
4. The method according to claim 1, characterized in that The initiator used in step S2 is persulfate.
5. The method according to claim 4, characterized in that The initiator is one or more selected from potassium persulfate, sodium persulfate and ammonium persulfate.
6. The method according to claim 1, characterized in that In step S2, after the initiator is added, ultrasonic mixing is performed.
7. The method according to claim 1, characterized in that In step S4, the water washing is to soak the proton exchange membrane obtained in step S3 in water for 24 to 48 hours, during which the water is changed 4 to 8 times.
8. The method according to claim 1, characterized in that Step S5 has one or more of the following features: The acid washing is to soak the washed proton exchange membrane in an acid solution for 1 to 3 hours; The concentration of the acid solution is 0.01 mol / L to 1 mol / L; The acid solution is dilute sulfuric acid; The drying is performed at 40-60°C for 1-3 hours; The hydrogel composite proton exchange membrane obtained in step S5 is 2-10 μm thicker than the proton exchange membrane before immersion in step S1.
9. A hydrogel composite proton exchange membrane prepared by the method according to any one of claims 1 to 8.
10. An all-vanadium redox flow battery comprising the hydrogel composite proton exchange membrane according to claim 9.
